Controlling Task Dependency as a Risk Mitigation Process - Hasni, Mohamed S M; Köprübaşı, Turhan (Advance Academic Publisher, 2018)
The construction of highly reliable software projects requires that these projects meet the objectives for which they have been set, and therefore failure to meet any of these objectives and needs will make the software project prone to failure. Thus, ignoring strong needs and not including users adequately especially in identifying their needs and tracking their dependencies clearly can be considered one of the main risks of failure. In this paper, we present a systematic approach to addressing this phenomenon and its mitigation mechanism.